A better inferior vena cava filter retrieval rate: A retrospective study in a single-center institution. (July 2020) - Cao, Pengkai; Li, Yunsong; Liu, Xiangdong; Li, Liang; Li, Haitao; Zhang, Xianchao; Hao, Qingchun; Zhang, Yanrong
Purpose: To determine practice patterns of inferior vena cava filters (IVCFs), retrieval rates, and reasons why retrievable-IVCFs (R-IVCFs) are kept permanent. Methods: A total of 399 patients who received IVCFs at Third Hospital of Hebei Medical University from January 2017 to December 2017 were registered and retrospectively studied. Date of demographics, baseline medical history, dwell time, reasons why R-IVCFs were kept permanent, and R-IVCFs thrombus were collected. Results: A total of 399 IVCFs were placed during the study period including 27 permanent IVCFs and 372 R-IVCFs. Among all patients who received R-IVCFs, the mean dwell time was 18.25 ± 16.60 days, follow-up rate was 96.24% (358/372), and 337 R-IVCFs were attempted to be removed. Except one, 336 R-IVCFs were retrieved successfully (336/372, 90.32%). Sixty-four R-IVCFs thrombi were found during retrieval including 53 small-size thrombi (< 1 cm × 1 cm) and 13 large-size thrombi (>1 cm × 1 cm). Fifty-three R-IVCFs with small-size thrombi were removed successfully with no additional treatments. Twelve large-size thrombi were retrieved successfully after catheter-directed thrombolysis. Conclusions: With good follow-up, the retrieval rate could be improved to 90.32%. The main reasons why R-IVCFs were kept permanent were to avoid losing follow-up and overcome inappropriate selections of indications or IVCF types. And R-IVCFs with thrombus could be removed safely.